Answer:
Step-by-step explanation:
x^2 + 3x + 2 = (x+1)(x+2)
x^2 + 4x + 3 = (x+1)(x+3)
LCM = (x+1)(x+2)(x+3) = (x^2 + 3x + 2) (x+3) = x^3 + 6x^2 + 11x + 6
An expression is defined as a set of numbers, variables, and mathematical operations. The solution of (4 x 3)² ÷ 6 is 24.
<h3>What is an Expression?</h3>
In mathematics, an expression is defined as a set of numbers, variables, and mathematical operations formed according to rules dependent on the context.
The solution of the expression (4 x 3)² ÷ 6 is,
(4 x 3)² ÷ 6
= (12)² ÷ 6
= 144 ÷ 6
= 24
Hence, the solution of (4 x 3)² ÷ 6 is 24.
Learn more about Expression:
brainly.com/question/13947055
#SPJ1
The correct answer is letter D, Region D contains the solution for the system of inequalities.
Answer:
I'm pretty sure it's 1,1.
Step-by-step explanation:
So if I understand correctly, she had 7 1/8 pounds of birdseed and used 3/8 pound.
Convert the 7 1/8 to an improper fraction [(8*7)+1]/8 =57/8
57/8 - 3/8 = 54/8, which is 6 6/8 which reduces to 6 3/4 pounds left
If she had 7 pounds of birdseed and used 3/8 pounds, you need to find a common denominator to subtract if you can't do it in your head. 8 would be the common denominator, so:
56/8 - 3/8 = 53/8, which is 6 5/8 pounds left